2022
DOI: 10.3390/curroncol29020042
|View full text |Cite
|
Sign up to set email alerts
|

Reproductive Health Experiences of Females Diagnosed with Young-Onset Colorectal Cancer: A Multi-Method Cross-Sectional Survey

Abstract: Objective: Given the increasing risk of young-onset colorectal cancer (yCRC) among adults under 50 years, it is important to understand impacts on reproductive health. Our objective was to assess experiences with reproductive health after yCRC diagnosis among females. Methods: We conducted a cross-sectional study among females, 18 years or older, who have been diagnosed yCRC and are able to communicate in English. Data were gathered using an online survey involving both quantitative (e.g., multiple choice) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
2
2
0
Order By: Relevance
“…Our findings are particularly relevant to health care systems similar to Australia's where primary care plays a central role in facilitating access to secondary care services. The life‐stage considerations identified in our study were consistent with existing literature, including reproductive plans, 30 career development, 28 and care of young families 29 . While previous studies have identified these factors as important in treatment decisions, our study suggests they are also important in diagnostic decisions, with care of young children and busy employment schedules as reasons for prolonging time to testing.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Our findings are particularly relevant to health care systems similar to Australia's where primary care plays a central role in facilitating access to secondary care services. The life‐stage considerations identified in our study were consistent with existing literature, including reproductive plans, 30 career development, 28 and care of young families 29 . While previous studies have identified these factors as important in treatment decisions, our study suggests they are also important in diagnostic decisions, with care of young children and busy employment schedules as reasons for prolonging time to testing.…”
Section: Discussionsupporting
confidence: 86%
“…While previous work from North America has identified stage-oflife considerations associated with young-onset CRC treatment, 28,30 to our knowledge this is the first time they have been explored in the Australian context in the diagnostic period. Our findings are particularly relevant to health care systems similar to Australia's where primary care plays a central role in facilitating access to secondary care services.…”
Section: Y09mentioning
confidence: 94%
“…European Society for Medical Oncology guidelines state that, “all cancer patients of reproductive age should receive complete oncofertility counselling as early as possible in the treatment planning process, irrespective of type and stage of disease.” 31 However, our study demonstrates a gap between guidelines and clinical practice in early‐onset CRC. Similarly, a study published in 2022 found that 43.6% of female early‐onset CRC patients had no discussion with HCP about this area of their lives ( n = 101, 24% of these receiving active treatment) 32 . Our findings also highlight conflict between whether to prioritise cancer treatment or fertility preservation in early‐onset CRC patients, as has been observed in other cancers 33 …”
Section: Discussionsupporting
confidence: 73%
“…Similarly, a study published in 2022 found that 43.6% of female early-onset CRC patients had no discussion with HCP about this area of their lives (n = 101, 24% of these receiving active treatment). 32 Our findings also highlight conflict between whether to prioritise cancer treatment or fertility preservation in early-onset CRC patients, as has been observed in other cancers. 33 Our findings show a lack of discussion regarding sex and intimacy.…”
Section: P9 Age 40-49mentioning
confidence: 58%